Optimization of Viability Treatment Essential for Accurate Droplet Digital PCR Enumeration of Probiotics - Kiefer, Anthony; Tang, Peipei; Arndt, Samuel; Fallico, Vincenzo; Wong, Connie (Frontiers in Microbiology, 2020)
Improvements offered by viability droplet digital PCR (v-ddPCR) include increased precision, specificity and decreased time to results making for an attractive alternative method to traditional plate count enumeration of probiotic products. A major hurdle faced in v-ddPCR, however, is distinguishing between live and dead cells. The objective of this study was to evaluate a combination of PMA and EMA (PE51) for viability treatment of freeze-dried probiotic powders. Lactobacillus acidophilus La-14 and Bifidobacterium animalis subsp. lactis Bi-07 were analyzed over a 2-log concentration gradient to investigate the efficiency of PE51 across genus and assay targets. Results suggest a need to optimize viability dye concentration based on the genera of the organism, but also the assay target, even when analyzing the same organism. When optimized for PE51 concentration, strain specific v-ddPCR assays for both La-14 and Bi-07 were demonstrated to agree with plate count enumeration results. In conclusion, while these v-ddPCR assays require highly specific optimization, they are better suited for the future of the probiotic industry and are suggested to be implemented in probiotic product testing.